A hagyatéki eljárás alapjai és lefolytatása, különös tekintettel a feladatok megoszlására az eljárás során, valamint a jogorvoslat egyes lehetőségeire - Ferenczi, Fanni (Debreceni Jogi Műhely, 2016)
As the title suggest, the study intends to provide a summarized overview on the regulation of probate proceeding. The legal nature of out-of-court proceeding and the various stages of the procedure are briefly presented in this study. The procedural steprelated to the task of inventory taking and each stage of the proceeding related to the notary public are explained too. Finally, the study includes an overview of the available remedies (like the certain aspects of appeal and the possibility of retrial) and the basic rules on enforcement of inheritance claims.